Further Evidence of a Brown Dwarf Orbiting the Post-Common Envelope Eclipsing Binary V470 Cam (HS 0705+6700) - Bogensberger David; Clarke Fraser; Lynas-Gray Anthony Eugene (Open Astronomy, 2017)
Several post-common envelope binaries have slightly increasing, decreasing or oscillating orbital periods. One of several possible explanations is light travel-time changes, caused by the binary centre-of-mass being perturbed by the gravitational pull of a third body. Further studies are necessary because it is not clear how a third body could have survived subdwarf progenitor mass-loss at the tip of the Red Giant Branch, or formed subsequently. Thirty-nine primary eclipse times for V470 Cam were secured with the Philip Wetton Telescope during the period 2016 November 25th to 2017 January 27th. Available eclipse timings suggest a brown dwarf tertiary having a mass of at least 0.0236(40) M⊙, an elliptical orbit with an eccentricity of 0.376(98) and an orbital period of 11.77(67) years about the binary centreof- mass. The mass and orbit suggest a hybrid formation, in which some ejected material from the subdwarf progenitor was accreted on to a precursor tertiary component, although additional observations would be needed to confirm this interpretation and investigate other possible origins for the binary orbital period change.